(+)‐Cinchonine‐Decorated Dendrimers as Recoverable Organocatalysts. Issue 17 (6th August 2015) - Rull, Jordi; Casals, Martí; Sebastián, Rosa M.; Vallribera, Adelina; Majoral, Jean‐Pierre; Caminade, Anne‐Marie
Abstract First‐ and fourth‐generation phosphorus dendrimers decorated on their surface with (+)‐cinchonine moieties for the use as organocatalysts have been prepared. The first‐generation dendrite showed the highest activity and enantioselectivity in the α‐amination of several β‐dicarbonyl compounds. A positive dendritic effect was observed. Its recovery and reuse over 10 cycles was demonstrated without loss of activity. Preliminary studies of the scope of the reaction have been performed.